Use of Biotechnology in Forestry Breeding Programs for Natural Resources and Biodiversity Conservation: Creating Super Trees for the Future - Montalbán, Itziar A. (2020)
Owing to the increasing human population and the increasing global demand for wood, its consumption is exceeding the natural rate of regeneration in many areas worldwide. Despite only 3% of the world’s forested land is plantation forest, plantations are highly productive; and with further improvement in genetic composition of planting stock as well as applying biotechnology, additional productivity increases can be obtained. For this reason, it is necessary to enrich traditional breeding programs with biotechnological tools able to increase the quantity and quality of the forestry plants produced. FAO’s definition of forest biotechnology encompasses different techniques for cloning forest trees. Forestry companies are currently considering clonal propagation as a good source of forestry plants. Clonal propagation can be achieved by various means: grafting, rooting of cuttings, coppicing, or in vitro propagation. Several methods of clonal propagation are being practiced with conifers. Along this chapter, a summary of some of the different approaches to improve Pinus spp. clonal propagation will be described, particularly those made in our laboratory.